FIRM-LEVEL TRAITS AND THE ADOPTION OF COMPUTERISED ACCOUNTING INFORMATION SYSTEM AMONG LISTED MANUFACTURING FIRMS IN NIGERIA (Journal of Global Accounting, 2023)
Inadequate investment in computerised accounting systems (CAIS) remain one of the most noticeable factors that impair the competitive edges of manufacturing firms. Thus, the study intends to ascertain the effect of firm profitability, firm size, firm capital turnover and firm liquidity on the level of accounting software used by listed manufacturing firms in Nigeria. Ex-post facto research design was used on a sample size of 21 listed manufacturing firms purposively selected from a population frame of 34 listed industrial goods and consumer goods firms on the Nigerian Exchange Group. Secondary data were collected from the 2012 to 2021 financial statements of sampled firms. The result of the Prais-Winsten regression conducted at 5% significance level revealed the following: firm profitability has no significant effect on the adoption of CAIS (Pro>|z| = 0.154); firm size has a significant positive effect on the adoption of CAIS (Pro>|z| = 0.000); firm capital turnover has a significant positive effect on the adoption of CAIS (Pro>|z| = 0.024); firm liquidity has a significant positive effect on the adoption of CAIS among listed manufacturing firms in Nigeria (Pro>|z| = 0.027). It was concluded that manufacturing firms that have satisfactory resources attain the organisational readiness status which enhances the adoption of better computerised accounting information system. The study recommends the following: managers of manufacturing companies should extend their support towards implementing and maintaining high quality accounting IT infrastructure in the firms; investors in manufacturing firms should invest in those firms whose level of adoption of CAIS is relatively adequate for the purpose of enhancing the quality of the firms’ financial reporting process; accounting software technicians should model accounting IT infrastructure in a way that they can be afforded by firms with slender financial conditions; professional accountants who man accounting IT infrastructure in firms should be regularly trained to meet up with the recent changes in computerised accounting information system.
Keywords: Computerised Accounting Information System; Firm Capital Turnover; Firm Profitability; Firm Size; Firm-Level Traits